Modeling of Corrosion Kinetics of Mild Steel in Hydrochloric Acid in the Presence and Absence of a Drug Inhibitor - Aljbour,Salah H. (2016)
Cefixime was investigated as a corrosion inhibitor for mild steel in an hydrochloric acid solution. The results revealed that the order of reaction is 0.427, with activation energy found to be 41.7 kJ/mol. Cefixime was effective in increasing the inhibition efficiency for all inhibition concentrations. The corrosion rate profile was found to be second- order kinetics with respect to corrosion activity.